Peningkatan Hasil Belajar Pendidikan Agama Islam Siswa Dengan Menggunakan Metode Diskusi Di SMAN 1 Kecamatan Payakumbuh - Prima Sari, Dina (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to examine the impact of applying the group discussion method on students' learning outcomes in Islamic Education at class X E, SMAN 1 Payakumbuh. This research employs a classroom action research method carried out in two cycles, each consisting of planning, implementation, observation, and reflection. The results show that the group discussion method can improve students' learning outcomes. The average score of students in Cycle I was 73.84, and in Cycle II, it increased to 84.62. This indicates that the group discussion method effectively enhances students' understanding and skills in expressing opinions and asking questions. However, despite the improvement, some students did not meet the Minimum Completion Criteria (KKM). Overall, the application of this method has proven to be effective in improving students' learning outcomes in Islamic Education